2013
DOI: 10.7243/2052-6954-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria parasitaemia and methaemoglobin levels among blood donors in Sokoto, Nigeria

Abstract: Background: Safety of blood and blood products is of global concern in transfusion medicine especially as it concerns the transfusion transmissible malaria infection scourging the tropics. Malaria parasite also disrupts haemoglobin pigment converting haemoglobin to non functional methaemoglobin. This study was taken to determine the prevalence of malaria parasitaemia and methaemoglobin level among blood donors attending Usmanu Danfodiyo University Teaching Hospital Sokoto (UDUTH). Method: Two hundred and twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Thus, the results presented here appear to be more in line with two studies in Nigeria which reported more modest increases in MetHb levels in malaria: one study in 228 blood donors found a significantly higher MetHb level in Plasmodium falciparum positive individuals with a mean of 2.7% as compared to negative controls, with a mean of 2% [15] while another study in children showed raised MetHb levels in malaria (3.2%) as compared to no malaria (1.5%) [32]. …”
Section: Discussionsupporting
confidence: 90%
“…Thus, the results presented here appear to be more in line with two studies in Nigeria which reported more modest increases in MetHb levels in malaria: one study in 228 blood donors found a significantly higher MetHb level in Plasmodium falciparum positive individuals with a mean of 2.7% as compared to negative controls, with a mean of 2% [15] while another study in children showed raised MetHb levels in malaria (3.2%) as compared to no malaria (1.5%) [32]. …”
Section: Discussionsupporting
confidence: 90%
“…The absorbance at 630 nm (T1) was measured before (T1) and after (T2) the KCN was added. Met-Hb content was expressed as a percent calculated on the basis of the equation [100(S1-S2)] / [10(T1-T2)] (15)(16).…”
mentioning
confidence: 99%
“…Sick neonates who undergo blood transfusion in sub-Saharan Africa especially in Nigeria are at risk of TM. This is because several studies have shown that the prevalence rate of malaria parasitaemia in donor blood across the SSA countries and in Nigeria is high with a range of 0.7%-55%[ 6 ] and 4.7%-74.1%[ 7 11 ] in SSA and Nigeria respectively. Also, routine screening of donor blood for malaria parasites prior to transfusion is currently not being practiced.…”
Section: Introductionmentioning
confidence: 99%